On partial derivative-Neumann's problem in generalized functions framework - Toledo, J. [UNESP] (Gordon Breach Sci Publ Ltd, 1998)
In this paper, we show that the equation delta u/delta (z) over bar + Gu = f, where the elements involved are in generalized functions context, has a local solution in the generalized functions context.
Keywords: Generalized functions; Local solutions of partial differential equations